Implied volatility spillover in agricultural and energy markets - Luensmann, Claire (Kansas State University, 2014)
In recent years, the agricultural markets have been subject to increased prices and unusual levels of elevated volatility. One likely driver of this is the mandated ethanol expansion in the Energy Policy Act of 2005. Previous research has identified relationships in market prices and variability between the energy and grain markets, but little has been done to evaluate volatility spillover across a broader spectrum of agricultural commodities. Additionally, few studies have assessed causal linkages across market implied volatilities. This research examines implied volatility spillover in futures markets across major agricultural commodities and energies. The analysis also determines the time path and magnitude of volatility translation across the markets and compares the causal relationships between pre-ethanol boom and post-ethanol boom time periods. Granger causality tests are conducted using multivariate and bivariate vector autoregressive modeling techniques, and impulse response functions are employed to obtain time paths of the reactions. Overall, results indicate that strong implied volatility spillover relationships exist between the grain markets and between the live cattle and feeder cattle markets. The analysis also finds that the agricultural markets have evolved from lean hogs being the primary volatility leader in the pre-ethanol boom era to corn being the primary volatility leader in the post-ethanol boom era. Despite a high correlation between crude oil and corn volatilities in the post-ethanol boom time period, the causal linkage between the two commodities’ volatilities may not be as definite as other literature suggests.
Keywords: Implied volatility; Volatility spillover; Commodity markets; Economics, Agricultural (0503)